2016
DOI: 10.1111/jfbc.12307
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy ofHammada scopariaExtract Against Ethanol Induced Renal Dysfunction in Wistar Rats

Abstract: Renoprotective effect of Hammada scoparia extracts was evaluated in Wistar albino rats which were distributed into five groups of six animals each. Three groups were treated simultaneously with ethanol 35% (4 g/kg) and plant extracts for 4 weeks. Other animals (EtOH) were given ethanol alone, and the control received 0.9% NaCl. The results showed that methanolic extract attenuated the increase of TBARS in kidneys, and also enhanced antioxidant status of the rats by increasing the levels of superoxide dismutase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In the search for substances that might reduce cell adhesion-mediated drug resistance (CAM-DR), researchers investigated the effect of Hammada scoparia extracts on adherent or suspended leukemic cells. Results demonstrate that Hammada scoparia flavonoid fraction and its constituent rutin stimulate apoptosis, particularly in adherent leukemic cells, and reduce CAM-DR (Ezzeddine et al, 2016).…”
Section: Antileukemic Activitymentioning
confidence: 87%
See 2 more Smart Citations
“…In the search for substances that might reduce cell adhesion-mediated drug resistance (CAM-DR), researchers investigated the effect of Hammada scoparia extracts on adherent or suspended leukemic cells. Results demonstrate that Hammada scoparia flavonoid fraction and its constituent rutin stimulate apoptosis, particularly in adherent leukemic cells, and reduce CAM-DR (Ezzeddine et al, 2016).…”
Section: Antileukemic Activitymentioning
confidence: 87%
“…Hammada scoparia is widely used in traditional medicine in North Africa (Table 2) to prevent many diseases, such as hepatitis, inflammation, and obesity (Ezzeddine et al, 2016). Several traditional applications have revealed that extracts of Hammada scoparia have anti-cancer and anti-diabetic properties (Bouaziz et al, 2016;Boulanouar et al, 2013;Hamza et al, 2019;Saidi et al, 2015;Taïbi et al, 2020).…”
Section: Ethnomedicinal Usesmentioning
confidence: 99%
See 1 more Smart Citation